Recognising Reading Comprehension Outlook and Solution for Gen Z - Fauzan (Arus Jurnal Sosial dan Humaniora, 2024)
Reading comprehension is an essential ability for a child's growth and development. Teaching youngsters to read English literature is a crucial skill. The objective of this essay is to examine recent and seminal research on reading challenges from three perspectives: cognitive, social and cultural, and interactive. The three views are examined, and their contribution to our understanding of how to help children with reading challenges is discussed. This article looks at the reasons of reading comprehension problems, the implications, and how to improve this vital skill. This study examines the three perspectives and the contributions they offer. The contributions of these views are addressed in relation to two contemporary evaluation instruments. The findings in this paper have ramifications for instructors who teach students at risk for dyslexia and developmental language impairments.